Injecting drug users who are (un)aware of their HIV serostatus: findings from the multi-center study AjUDE-Brasil II - Ferreira Aline Dayrell; Caiaffa Waleska Teixeira; Bastos Francisco I.; Mingoti Sueli Aparecida (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
This study aimed to characterize the profiles of injecting drug users (IDUs) who were unaware of their HIV serostatus, given the importance of this information for prevention strategies, especially in this vulnerable population, key to the HIV/AIDS dynamic. As part of a cross-sectional multi-city survey, IDUs were interviewed and HIV-tested by the ELISA technique. IDUs were categorized according to knowledge of their own HIV status as either aware or unaware. Means, averages, and proportions were compared between the groups using bi- and multivariate analyses. Of 857 IDUs interviewed, 34.2% were unaware of their HIV serostatus. Those who were unaware were more likely: to have been recruited at sites where the HIV prevalence rate was considered medium (> 10 to 50%; odds ratio = 8.0) or high (> 50%; 4.0); to be illiterate (OR = 4.54); to have no prior HIV test (OR = 2.22); to be male (OR = 1.81); and to have been enrolled more recently in syringe-exchange programs (OR = 1.69). HIV prevention programs should target both individuals at risk and HIV-positive individuals. Programs to expand access to HIV testing are pivotal and should be tailored to specific contexts and populations.